Ober Geometrie des quasilinearischen Systems der Differentialgleichungen zweiter Ordnung - Lupeikis, Z. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: З. Ю. Лупеикис. О геометрии квазилинейных систем дифференциальных уравнений второго порядка Z. Lupeikis. Antros eilės kvazitiesinių diferencialinių lygčių sistemų geometrijos klausimu